Ambedkar's perspective on Buddhism and other religions - Singh, S. k. (New Delhi Innovative, 2023)
Just as there are billions of people on this planet, there are also billions of different dispositions and inclinations. From the Buddhist point of view, a wide choice of religions is needed to suit the varied needs of different people. Buddhism recognizes that all religions share the same aim of working for the well-being of mankind. Ambedkar converted to Buddhism in 1956. For two decades, he studied all major religions to conclude Buddha and his teachings allowed reform. Ambedkar compares the four religious teachers to find another distinction between Buddha and the rest. He says that both Jesus and Mohammed claimed that what they taught was the word of God and (thus) was beyond question. Krishna was, according to his own assumption, a God of Gods and therefore the question of infallibility did not even arise. The Buddha claimed no such infallibility for what he taught. In the Mahaparinibbana Sutta, he told Ananda that his followers should not accept his teaching as correct and binding merely because they emanated from Him. Being based on reason and experience, the followers were free to modify or even to abandon any of his teachings if it was found that at a given time and in given circumstances they do not apply. The present book is an attempt to describe Ambedkar$1 (Bs overview on religions and the reason to choose Buddhism over other religions. This is an important guide for all those interested in Dalit and Ambedkar Studies.s
Keywords: Religion- Buddhism; Religious Political Philosophy; Ambedkar & Buddhism; Dr. B. R. Ambedkar (1891-1956)